Internet of things for energy efficiency and personalization - Ferreira, J. C. (Intelligent Environments 2016, 2016)
The present work presents a home energy management system (HEMS) that based on an Internet of Things will allow appliances to be turned on or off by remote commands. This approach is essential for a sustainable planet with the fast growing implementation of intermittent renewable energy sources, like wind and solar. This renewable energy sources have an intermittent behavior, so one solution to this problem is an EMS that tries to fit production to energy consumption. In this research work we propose a solution based on the standard OpenADR and a network of sensors to handle this problem, creating a platform based on internet-of-things capable to turn-on or off electrical devices based on a central decision process that meets the requirements of energy producers and consumers. Producers can provide energy according to the consumer's requirements and take part of energy production and costs fluctuations. Based on an OpenADR standard for energy data exchange and a central cloud server, a list of services are provided to handle these transactions, with georeferenced information to minimize energy losses in the distribution process. Furthermore, mobile devices can passive collect user mobility data to optimize energy efficiency, heating or cooling the house before users return home, thus, generating energy personalized services.